Inside BAR (The Biblical archaeology review, 1983)
On the eighth day of the Hebrew month of Elul (August 18, 1983), the Israeli authorities opened to the public a building that had been closed for 1,913 years to the day. The building, in ancient Jerusalem’s Upper City, was a workshop that was stormed by Roman soldiers on the eighth of Elul, 70 A.D., […]